Linguistic and Ontological Issues at the Heart of the Nunavik Itinerant Court: The Role of Interpreters as Cultural Mediators - Laneuville, Pascale; Miot-Bruneau, Allie; Martineau, Isabelle; Hervé, Caroline (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2025)
In this International Decade of Indigenous Languages (2022–2032)—as proclaimed by the United Nations General Assembly—it is important to note that the Inuit of Nunavik (Arctic Quebec) still widely speak their own language, Inuktitut, while understanding the two colonial languages, English and French, to greatly varying degrees. The Court of Québec has jurisdiction in the region over criminal matters, whereas different legal texts protect the right of Inuit to court interpretation, including the provincial and federal Charters of Rights and Freedoms. In this paper, we address the linguistic challenges of interpreting at the Nunavik Itinerant Court, with the aim of shedding light on the ontological conflicts at the heart of the justice system. We also examine the meaning of “justice” for Inuit. To that end, we use the results of research by the Sentinel North Research Chair on Relations with Inuit Societies (Université Laval).